Genetic predisposition to MDS: diagnosis and management - Furutani, Elissa (Hematology Am Soc Hematol Educ Program, 2019)
Myelodysplastic syndromes (MDS) are a heterogeneous group of disorders characterized by clonal hematopoiesis with a propensity to evolve into acute myeloid leukemia. MDS presenting in children and young adults is associated with features clinically and biologically distinct from MDS arising in older adults. MDS presenting in children and young adults is associated with a higher likelihood of an underlying genetic predisposition; however, genetic predisposition is increasingly recognized in a subset of older adults. The diagnosis of a genetic predisposition to MDS informs clinical care and treatment selection. Early diagnosis allows a tailored approach to management and surveillance. Genetic testing now offers a powerful diagnostic approach but also poses new challenges and caveats. Clinical expertise in these disorders together with scientific expertise regarding the affected genes is essential for diagnosis. Understanding the basic mechanisms of genetic predisposition to myeloid malignancies may inform surveillance strategies and lead to novel therapies. The cases presented in this article illustrate challenges to the diagnosis of germline genetic predisposition to MDS and how the diagnosis affects clinical management and treatment.